Autoconhecimento de crenças: empirismo, racionalismo e racionalidade - Barcelos, Róbson da Rosa (2017)
Self-knowledge is the cognitive ability of the agent to know his or her own mental states. There are several types of mental states, and there is a method for the knowledge of each type. The focus of this dissertation is on the knowledge of one‘s own beliefs. With this goal in mind, we present the empiricist and the rationalist approaches to the knowledge of one‘s own beliefs. Empiricist theories of self-knowledge proposes introspection as the method for the knowledge of one‘s own beliefs. However, there are issues related to the phenomenology of belief – what it is like to believe that p? The best rationalist theories of self-knowledge proposes that an agent ―look outwards to constitute her own mind and her own belief. Our final question is about the relationship between knowledge of one‘s beliefs and rationality. Burge (2013) requires that, in order to be rational, one must have self-knowledge. We argue that the kind of rationality specified by Burge is too demanding. As agents in the realm of common life, we have incomplete understanding of our own doxastic mental states, but that is not a problem for the knowledge of our own beliefs as dispositions, since they does not come from rational deliberation; nevertheless, we are responsible and our beliefs as commitments. Both kinds of belief can be known by the transparency method. We conclude claiming that the transparency method is enough for the self-knowledge of doxastic mental state and ensuring the rationality of the agent.